If #sinA*sin(B-c)=sinC*sin(A-B)# then show that # a^2,b^2,c^2# are in AP.?

Answer 1
#sinA*sin(B-C)=sinC*sin(A-B)#
#=>2sin(pi-(B+C))*sin(B-C)=2sin(pi-(A+B))*sin(A-B)#
#=>2sin(B+C)*sin(B-C)=2sin(A+B)*sin(A-B)#
#=>cos(2C)-cos(2B)=cos(2B)-cos(2A)#
#=>1-2sin^2(C)-1+2sin^2(B)=1-2sin^2(B)-1+2sin^2(A)#
#=>sin^2(B)-sin^2(C)=sin^2(A)-sin^2(B)#
#=>4R^2sin^2(B)-4R^2sin^2(C)=4R^2sin^2(A)-4R^2sin^2(B)#
#=>b^2-c^2=a^2-b^2#

This proves that

# a^2,b^2,c^2# are in AP
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

Given the equation sinAsin(B-c)=sinCsin(A-B), let's start by expanding both sides using the trigonometric identity: sin(x - y) = sinxcosy - cosxsiny.

Expanding the left-hand side (LHS): sinAsin(B - c) = sinA(sinBcosc - cosBsinc) = sinAsinBcosc - sinAcosBsinc

Expanding the right-hand side (RHS): sinCsin(A - B) = sinC(sinAcosB - cosAsinB) = sinCsinAcosB - sinCcosAsinB

Now, equating LHS and RHS: sinAsinBcosc - sinAcosBsinc = sinCsinAcosB - sinCcosAsinB

sinAsinBcosc - sinCsinAcosB = sinAcosBsinc - sinCcosAsinB

sinAsinBcosc - sinCsinAcosB = sinAcosB(sinc - sinC)

Dividing both sides by sinA*cosB: cosc - sinC = sinc - sinC

c - C = c - C

Since both sides are equal, the equation is satisfied.

Now, we need to prove that a^2, b^2, and c^2 are in arithmetic progression (AP). We know that: a = 2RsinA b = 2RsinB c = 2R*sinC

where R is the radius of the circumcircle of triangle ABC.

Now, squaring each of these and rearranging: a^2 = 4R^2sin^2A b^2 = 4R^2sin^2B c^2 = 4R^2*sin^2C

Now, it's evident that: b^2 - a^2 = 4R^2*(sin^2B - sin^2A) c^2 - b^2 = 4R^2*(sin^2C - sin^2B)

Given sinAsin(B-c)=sinCsin(A-B), we can conclude that sin^2A = sin^2C. Hence, sin^2B - sin^2A = 0 and sin^2C - sin^2B = 0.

Therefore, b^2 - a^2 = 0 and c^2 - b^2 = 0, implying that a^2, b^2, and c^2 are in arithmetic progression.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7